Anti-Russian Sanctions in Global Economic Warfare - A. S. Lebedev (Vestnik MGIMO-Universiteta, 2022)
The article analyzes the discrepancy between the declared goals of sanctions against Russia and their practical effects. The author puts forward a hypothesis according to which the real purpose of the anti-Russian sanctions imposed after the start of Russia's special military operation in Ukraine is not to change the foreign policy of the Russian Federation but to weaken the country as much as possible by causing economic damage to it and destabilizing the domestic political situation. Under these conditions, it is reasonable to consider sanctions as an "economic war," which raises the question of the goals of such a war, the choice of optimal methods for its conduct, and ways to minimize damage to the national economy. The author distinguishes between "defensive" and "offensive" methods of economic warfare. The article argues that a country that has become the object of large-scale sanctions is unable to successfully resist them in the long term, relying solely on "defensive" mechanisms (for example, measures to support the economy). It must resort to "offensive" tools as well, for instance to the embargo for the export of goods that are of key importance for the stability of the economic model of the countries that initiated the sanctions.